Reflections to a psychologically disoriented society - Arboccó de los Heros, Manuel (2021)
Then, we compile a set of essays where we reflect critically, some of the most troubling subjects of our postmodern, technocratic, liquid, hyper-consumerist and chronic distresssocieties. Theuncertainty, permanent dissatisfaction, detachment, individualism and extreme relativism are some of the concepts portrayed in this work. It is clear an unfavourablediagnosis of our societyin individual and interpersonal psychological matters and recognizing realistically that we live more than uncertain times (covid-19 pandemic included). We ended this article by aimingfor individual and socio-family change to try to rise from this time of uncertainties and social roughness. Moreover, we consider that we must identify and know the social to better understandthe individual self of each human being. It is not enough to appeal to a personal change when the social machinery produces evils as we will see below. It hurts to say it but this current societydoes not promote health and that must be pointed out and denounced. We hope, we wish it wholeheartedly, humanist utopia can be realized slowly.